96.3k views
0 votes
Multiple-8ab^3(a^5b^4+6a^2b+3ab-6)

1 Answer

3 votes

The question is:


8ab^3\mleft(a^5b^4+6a^2b+3ab-6\mright)​

To multiply we would use distributive property, which is basically:


a(b+c+d)=ab+ac+ad

Also, not when multiplying exponents with same base, you add the exponents, such as:


a^x* a^y=a^(x+y)^{}

Now, let's multiply:


\begin{gathered} 8ab^3(a^5b^4+6a^2b+3ab-6)​ \\ =8ab^3a^5b^4+(8)(6)ab^3a^2b+(8)(3)ab^3ab-(6)(8)ab^3 \\ =8a^6b^7+48a^3b^4+24a^2b^4-48ab^3 \end{gathered}

User Kjsebastian
by
5.1k points